Word-of-Mouth Communication and Percolation in Social Networks - Campbell, Arthur (American Economic Review, 2013)
This paper develops a model of demand, pricing and advertising in the presence of social learning via word-of-mouth communication between friends. In the model consumers must receive information about a monopolist's product in order to consider purchasing it. The presence of word-of-mouth is not sufficient for demand to be more elastic and prices to be lower compared to an informed population. I derive the comparative static results of connectivity, mean-preserving spread of friendships, and clustering of friends on prices. The optimal targets for advertising are not, generically, the individuals with the most friends. (JEL L12, L14)